β-CARBOLINE PRODUCTION FROM IN VITRO REGENERATED PEGANUM HARMALA L. PLANT - Onlu, Seyma; Bingol, Omer; Turker, Musa; Ozdemir, Fethi Ahmet (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2018)
Peganum harmala L. seeds were germinated in hormone free sterile MS medium. Root, shoot tip, leaf, petiole, hypocotyl, cotyledon and nod explants excised from in vitro regenerated plants were incubated in MS medium supplemented with 1 mg/l and 2 mg/l 2,4-D for callus production. Hypocotyl and cotyledon explants produced callus and untreated callus was accepted as control for the comparison of beta-carboline alkaloids production extracted from different samples. Callus were exposed to cold and dark conditions and incubated in MS medium supplemented with 2 mg/l ABA, 1 mg/l ABA, 1 mg/l NAA and 1 mg/l BAP in different batches to increase beta-carboline alkaloid production. Seeds were germinated in soil ambient condition. beta-carboline alkaloids; harmalol, harmine and harmaline were extracted from seeds, plants grown in soil, callus grown in MS medium supplemented with 2,4-D, callus incubated MS medium supplemented with NAA, BAP, ABA and callus exposed cold and dark condition. The extracts were quantitatively analysed with HPLC. The highest alkaloid concentrations were determined in vivo seeds and plants grown in soil. However, alkaloid production in callus tissues is also promising. Harmalol and harmine concentration decreased with cold treatment but increased with ABA treatment compared to that of the control. Harmaline was increased with cold treatment, but dramatically decreased in all treatment that callus is exposed.
Keywords: Peganum harmala L.; alkaloid; in vitro; HPLC; stress; ALKALOIDS; Environmental Sciences & Ecology